Electroporation as an Efficacy Potentiator for Antibiotics With Different Target Sites - Lovšin, Žana; Klančnik, Anja; Kotnik, Tadej (Frontiers in Microbiology, 2021)
Antibiotic resistance is a global health threat, and there is ample motivation for development of novel antibacterial approaches combining multiple strategies. Electroporation is among the promising complementary techniques – highly optimizable, effective against a broad range of bacteria, and largely impervious to development of resistance. To date, most studies investigating electroporation as an efficacy potentiator for antibacterials used substances permissible in food industry, and only few used clinical antibiotics, as acceptable applications are largely limited to treatment of wastewaters inherently contaminated with such antibiotics. Moreover, most studies have focused mainly on maximal achievable effect, and less on underlying mechanisms. Here, we compare E. coli inactivation potentiation rates for three antibiotics with different modes of action: ampicillin (inhibits cell wall synthesis), ciprofloxacin (inhibits DNA replication), and tetracycline (inhibits protein synthesis). We used concentrations for each antibiotic from 0 to 30× its minimum inhibitory concentration, a single 1 ms electric pulse with amplitude from 0 to 20 kV/cm, and post pulse pre dilution incubation either absent (≲1 min) or lasting 60 min, 160 min, or 24 h. Our data show that with incubation, potentiation is significant for all three antibiotics, increases consistently with pulse amplitude, and generally also with antibiotic concentration and incubation time. With incubation, potentiation for ampicillin was rather consistently (although with weak statistical significance) superior to both ciprofloxacin and tetracycline: ampicillin was superior to both in 42 of 48 data points, including 7 with significance with respect to both, while at 60 and 160 min incubation, it was superior in 31 of 32 data points, including 6 with significance with respect to both. This suggests that electroporation potentiates wall targeting antibiotics more than those with intracellular targets, providing motivation for in depth studies of the relationship between the mode of action of an antibiotic and its potentiation by electroporation. Identification of substances permissible in foods and targeting the cell wall of both Gram negative and Gram positive bacteria might provide candidate antibacterials for broad and strong potentiation by electroporation applicable also for food preservation.